Bioerosion and palaeoecological association of osteophagous insects in the Maastrichtian dinosaur Arenysaurus ardevoli. (21st December 2021) - Cruzado‐Caballero, Penélope; Canudo, José I.; De Valais, Silvina; Frigola, Jaime; Barriuso, Eduardo; Fortuny, Josep
Abstract : Bioerosions produced by the osteophagous diet of animals that fed on dinosaur bones are very scarce in the European fossil record. Herein we present bioerosion on hadrosaurid remains from the Maastrichtian Tremp Formation of the Pyrenean Basin, which is only the second such case recorded from the Iberian‐Occitan Plate besides a sauropod from the Jurassic‐Cretaceous of Valencia. The hadrosaurid fossil record is particularly rich in the Blasi sites of the Tremp Formation located in the municipality of Arén (Huesca, Spain). In this article, bones referred to the hadrosaurid Arenysaurus ardevoli from the Blasi‐3 site are analysed to shed light on the palaeoenvironment and on the presence of a palaeoecological interaction between the hadrosaurid carcase and osteophagous tracemakers. Bioerosions recorded on the bones comprise tunnels, roundish holes, and straight notches, similar to the traces attributed to necrophagous insects (cf. Cuniculichnus seilacheri ). Here, we record the first instance of the activity of these animals on dinosaur bones in the Upper Cretaceous of the Ibero‐Occitan Plate. The results presented lead us to infer that the Arenysaurus bones were possibly transported by a storm or similar event to the Blasi‐3 site, where they were exposed to post‐mortem biotic interactions (eaten and partially decomposed by dermestid beetles) for a prolonged time period before they were completely buried.